PERAN PERPANJANGAN HAK GUNA USAHA (HGU) DAN HAK GUNA BANGUNAN (HGB) DALAM MENJAMIN KEPASTIAN HUKUM BAGI INVESTOR: TINJAUAN EKONOMI DAN REGULASI - Gunawan Widjaja; Khalimi (Adisam Publisher, 2025)
The extension of Land Use Rights (HGU) and Building Use Rights (HGB) is an important mechanism in the Indonesian land system that contributes to ensuring legal certainty for investors. This study aims to examine the role of HGU and HGB extension regulations and their impact on legal certainty, which in turn affects investment decisions. The method used is a literature review with two main discussions, namely regulatory analysis and economic review. The results of the study indicate that clear and structured regulations on the extension of rights provide a strong legal basis for investors to utilise land in the long term. From an economic perspective, the certainty of the extension system can increase investment interest, facilitate access to financing, and encourage growth in strategic sectors. However, challenges in implementation, such as complex administrative procedures and inter-agency coordination issues, remain obstacles that need to be addressed. This study underscores the importance of regulatory harmonisation, procedural simplification, and the utilisation of digital technology in enhancing legal certainty and the investment climate in Indonesia.